SISTEM PRESENSI BERBASIS QR CODE DENGAN NOTIFIKASI WHATSAPP PADA PT. ANGKASA PURA KUPANG - Yappy William Joseph; Menhya Snae; Dewi Anggraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
YAPPY WILLIAM JOSEPH, QR Code-Based Attendance System with WhatsApp Notifications at PT. Angkasa Pura Kupang City. Supervised by MENHYA SNAE and DEWI ANGGRAINI. Angkasa Pura Indonesia El Tari Airport Kupang is a state-owned enterprise engaged in airport management and airport service operations at El Tari Airport. The problem faced is that the employee attendance system is still carried out manually using Microsoft Excel, making it prone to recording errors, delays in data recapitulation, and attendance fraud. Therefore, a real-time QR Code-based attendance system with WhatsApp notifications to supervisors is needed to improve employee discipline and simplify attendance monitoring. This system was developed using the PHP programming language, Bootstrap 5 Framework, WhatsApp application, and the waterfall method. The expected result is the creation of an attendance system that is more effective, efficient, accurate, and capable of minimizing employee attendance violations.